Local Structure Recovery of Chain Graphs after Marginalization - Qiang Zhao; Panpan Luo; Qing Xi (Discrete Dynamics in Nature and Society)
This paper discusses local structure recovery of chain graphs (CGs) when there exist unobserved or latent variables or after marginalization over observed variables. Under a condition presented in this paper, it is explained which edges and directions of edges in local structure can be recovered validly and which cannot after marginalization.